Organism profiles and empirical treatments for periprosthetic joint infections - Gongan Jiang; Weijun Wang; Yuhao Yang; Minghao Zhang; Yutao Yang; Qing Jiang (Journal of Orthopaedic Surgery and Research)
Abstract Objective Information on pathogens and sensitive antibiotics is crucial for treating periprosthetic joint infection (PJI), one of the most severe complications of joint arthroplasty. Lacking this information is not uncommon, and empirical antibiotic treatment should be adopted as a compromise. This study aimed to develop regional-specific antimicrobial regimens and provide a reference for empirical antibiotic treatment for PJI by retrospectively analyzing the pathogen profiles of PJI patients treated in our center and their antibiotic sensitivities. Methods PJI patients treated at our center from January 2018 to December 2024 were retrospectively recruited. Joint aspiration was performed preoperatively to collect synovial fluid for culture and differential cell counting, and synovial tissue samples were obtained intraoperatively from at least three different sites for culture. Patients were diagnosed according to the guidelines of the 2018 International Consensus Meeting and the European Bone and Joint Infection Society. The culture-positive rate, distribution of gram-positive pathogens, methicillin resistance, mixed infections, and multidrug resistance were analyzed. The effective coverage rates of antibiotics were determined, and appropriate empirical antibiotic regimens were proposed. Results A total of 255 PJI patients, comprising 104 males and 151 females, were included; 141 patients had hip PJI, and 114 had knee PJI. Among them, 224 patients (87.8%) had positive culture results. We isolated 335 pathogens, including 218 coagulase-negative staphylococcal infections (65.1%). Staphylococcus epidermidis was the most prevalent pathogen, with 86 isolates (25.7%), followed by Staphylococcus aureus, with 45 isolates (13.4%), and Streptococci, with 20 isolates (6.0%). In hip PJI, the most common pathogens were Staphylococcus epidermidis (50 isolates, 26.6%) and Staphylococcus aureus (30 isolates, 16.0%), and in knee PJI, Staphylococcus epidermidis was predominant (36 isolates, 24.5%). In terms of drug resistance, 48.1% of the staphylococcal strains were methicillin resistant, and 57.6% of the pathogens were multidrug resistant. Staphylococci showed 100% sensitivity to vancomycin and linezolid but were highly resistant to β-lactams and quinolones. In patients with acute postoperative PJI, the combination of vancomycin combined with ceftazidime was 98.4% effective. In patients with chronic PJI, vancomycin combined with imipenem and meropenem achieved effective coverage rates of 94.4% and 95.5%, respectively. The combination of linezolid with meropenem also achieved a 95.5% effective coverage rate. Conclusion Gram-positive bacteria were the predominant pathogens associated with PJI, with high rates of methicillin resistance and multidrug resistance. The combination of vancomycin and meropenem is an empirical antibiotic regimen for culture-negative chronic PJI patients in this region, with the combination of linezolid and meropenem as an alternative. For patients with culture-negative acute postoperative PJI, vancomycin combined with ceftazidime is suggested as the preferred empirical therapy.